The Influence of Entrepreneurial Orientation on Business Performance is Mediated by Differentiation Strategy and Cost Leadership Strategy in Silver MSMEs in Kotagede - Wahyuni, Endah; Sabihaini, Sabihaini; Astuti, Widhy Tri (Westscience Press, 2025)
This study aims to examine and analyze the influence of entrepreneurial orientation on the business performance of silver MSMEs in Kotagede by being mediated by differentiation strategies and cost leadership strategies. The research was conducted at the silver craft center of Kotagede Yogyakarta. The population of this study is all silver MSME actors in Kotagede as many as 45 MSMEs. Sampling uses total sampling. Data collection was carried out through questionnaires and data analysis using SEM-PLS. The results of the study found that entrepreneurial orientation has a positive and significant influence on business performance, differentiation strategy and cost leadership strategy. Differentiation strategies and cost leadership strategies are able to mediate the influence of entrepreneurial orientation on business performance in silver MSMEs in Kotagede. The limitation of this study is on the limited coverage of only one area, namely Kotagede, so the results are not general, besides that this study does not consider other control variables.